Global Dispersal Pattern of HIV Type 1 Subtype CRF01_AE: A Genetic Trace of Human Mobility Related to Heterosexual Sexual Activities Centralized in Southeast Asia. - Angelis, Konstantinos; Albert, Jan; Mamais, Ioannis; Magiorkinis, Gkikas; Hatzakis, Angelos; Hamouda, Osamah; Struck, Daniel; Vercauteren, Jurgen; Wensing, Annemarie M J; Alexiev, Ivailo; Åsjö, Birgitta; Balotta, Claudia; et al. (J Infect Dis, 2015)
BACKGROUND: Human immunodeficiency virus type 1 (HIV-1) subtype CRF01_AE originated in Africa and then passed to Thailand, where it established a major epidemic. Despite the global presence of CRF01_AE, little is known about its subsequent dispersal pattern. METHODS: We assembled a global data set of 2736 CRF01_AE sequences by pooling sequences from public databases and patient-cohort studies. We estimated viral dispersal patterns, using statistical phylogeographic analysis run over bootstrap trees estimated by the maximum likelihood method. RESULTS: We show that Thailand has been the source of viral dispersal to most areas worldwide, including 17 of 20 sampled countries in Europe. Japan, Singapore, Vietnam, and other Asian countries have played a secondary role in the viral dissemination. In contrast, China and Taiwan have mainly imported strains from neighboring Asian countries, North America, and Africa without any significant viral exportation. DISCUSSION: The central role of Thailand in the global spread of CRF01_AE can be probably explained by the popularity of Thailand as a vacation destination characterized by sex tourism and by Thai emigration to the Western world. Our study highlights the unique case of CRF01_AE, the only globally distributed non-B clade whose global dispersal did not originate in Africa.
Keywords: Asia, Southeastern; Cluster analysis; Databases, Factual; Europe; Heterosexuality; HIV Infections; HIV-1; Humans; Phylogeny; Phylogeography; Population Dynamics